Teaching as an Act of Persuasion (TAP) and Attitudinal Responses of English Language Teachers: Saudi Schools as a Case Study - Rehaiem, Jalel (Advances in Social Sciences Research Journal, 2016)
This research seeks to analyze the teaching-as-persuasion metaphor in a sample of Saudi schools. It investigates how teaching as persuasion relates to English language teaching and the effectiveness and viability of this metaphor as a teaching practice specifically in the Saudi educational context. Teaching as persuasion is a new pedagogical approach that is conducive to the requirements and challenges of the contemporary world and it traces its roots specifically from the changes that distinguish the current educational enterprise (Murphy, 2001, p.227). Generally, persuasion is a pragmatic concept through which individuals seek to stimulate a change in others by influencing their understanding and conceptions relative to several topics (Murphy, 2001, p.224). Persuasion, thus defined, is based on credible arguments and plausible evidence. Persuasion has also proven to have a role in meeting educational purposes. This role is advocated by many researchers including Murphy (2001) and it is shown in the instructor’s focus on convincing learners of the worth of learning by stimulating them to change their understanding and beliefs of diverse concepts and assumptions (Murphy, 2001, p.224).